Transparent nanocomposites with enhanced performances from poly(propylene carbonate) and silica. Issue 1 (9th August 2021) - Ma, Youmei; Zhang, Shuling
Abstract: In this study, silica nanoparticles with a refractive index matching PPC and a diameter smaller than the visible light wavelength were chosen to prepare enhanced PPC/silica nanocomposites by a simple melt compounding method. The result exhibited all the nanocomposites possessed excellent transparency (about 90%), even in the nanocomposite with a silica content of 10 wt%. For PPC/silica nanocomposites, the percolation threshold was determined to be 7.5 wt% based on the dynamic rheological behavior and percolation theory. Moreover, the overall performance of the PPC‐based nanocomposite with a silica content of 7.5% is the best. The optimal nanocomposite showed a Young's modulus of 3792 MPa, a yield strength of 46.5 MPa, a storage modulus of 3812 MPa and a highest temperature at maximum weight‐loss rate ( T max, 309°C). These characteristics are very important for potential commodity applications of PPC. Abstract : Transparent poly(propylene carbonate)/silica nanocomposites with enhanced mechanical and thermal properties were fabricated. Moreover, the percolation threshold was determined to be 7.5 wt% for poly(propylene carbonate)/silica nanocomposites.